Analysis of Changes in Learning Patterns Before and During the Covid-19 Pandemic using Descriptive Statistical Methods - Ningrum, Yulika Pramesti; Hadiono, Kristophorus (Sistemasi: Jurnal Sistem Informasi, 2023)
In early 2020, the world was faced with the Covid-19 pandemic. The biggest impact of the pandemic was felt by the education sector, which prompted the government to develop an online learning program. This online learning will certainly affect student learning patterns. This study aims to determine changes in learning patterns that occurred before and during the Covid-19 pandemic. This research involved students of Stikubank University Semarang, Faculty of Information Technology and Industry class of 2019. The data obtained was analyzed statistically descriptive quantitatively including calculations of mean, median, standard deviation, validity tests, reliability tests, and graphs using R language. Based on the results of validity tests and reliability test, all indicators are valid and reliable. The results of the descriptive analysis of the indicator tests show that learning patterns decreased between before and during the Covid-19 pandemic. The indicator for planning learning activities has changed to the sub-indicator bringing reference books. The indicators for participating in learning activities also changed in the sub-indicator present before lectures. The indicators for making schedules and study notes also underwent changes in the sub-indicators for making notes/summaries of material which decreased significantly. The indicator for taking the exam also experienced a change in the sub-indicator for studying with friends. While the learning evaluation indicators also experienced changes in the sub-indicators working on practice questions.